Using Langmuir-Schaefer deposition technique to improve the gas sensing performance of regiorandom polythiophene films - de Oliveira, Vinícius Jessé Rodrigues [UNESP]; Borro, Marcelo Soares [UNESP]; Rubim do Monte Jesus, Laura [UNESP]; Braunger, Maria Luisa [UNESP]; Olivati, Clarissa de Almeida [UNESP] (Elsevier, 2022)
Polythiophene derivatives are one class of conducting polymers widely tested for application in organic electronics, such as photovoltaic devices, organic light-emitting diodes, and chemosensors to gas and liquid analysis. Polythiophenes can be classified as regioregular or regiorandom, which is determined by the position of their side chains in the polymer backbone, and the regioregular configuration is usually preferred for studies in organic electronic applications. There are few reports in the literature using regiorandom polythiophenes as active layers of devices, all with doped or composite materials. In this context, we have fabricated Langmuir-Schaefer films of neutral regiorandom polyalkylthiophenes (P3AT), aiming to evaluate their electrical characteristics compared to the drop-casting technique. The goal was to test whether the Langmuir deposition technique could yield a higher level of organization, while still being mindful of their intrinsic disorder at the molecular level. As a proof-of-concept, the thin films were evaluated as gas sensing devices relying on their resistivity modulation in the presence of ammonia. The devices based on Langmuir-Schaefer films of the regiorandom P3AT showed higher responses to the gas than the ones fabricated by drop-casting, indicating that the organization at the molecular level achieved by the deposition technique improved the gas sensing performance.
Keywords: Conducting polymer; Gas sensor; Langmuir-Schaefer; Regiorandom polythiophene; Thin film